2005
DOI: 10.1186/1743-8454-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid may mediate CNS ischemic injury

Abstract: Background: The central nervous system (CNS) is extremely vulnerable to ischemic injury. The details underlying this susceptibility are not completely understood. Since the CNS is surrounded by cerebrospinal fluid (CSF) that contains a low concentration of plasma protein, we examined the effect of changing the CSF in the evolution of CNS injury during ischemic insult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
3
0
2
Order By: Relevance
“…Functional motor recovery has been identified when Alb is injected directly into the spinal tissue or via the intravenous route [21], but careful analysis should be performed with FITC-albumin injected via the intrathecal route which would address this concern. Indeed a similar study has identified both grey and white spinal matter labelling with FITC-albumin when administered via the intravenous route, confirming penetration at least into the intraspinal microcirculatory system [87]. Albumin is commonly used a drug delivery system in the clinical setting [88] and specific known binding sites with OA suggest a biological basis for the synergistic action between both molecules observed in this study [89].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Functional motor recovery has been identified when Alb is injected directly into the spinal tissue or via the intravenous route [21], but careful analysis should be performed with FITC-albumin injected via the intrathecal route which would address this concern. Indeed a similar study has identified both grey and white spinal matter labelling with FITC-albumin when administered via the intravenous route, confirming penetration at least into the intraspinal microcirculatory system [87]. Albumin is commonly used a drug delivery system in the clinical setting [88] and specific known binding sites with OA suggest a biological basis for the synergistic action between both molecules observed in this study [89].…”
Section: Discussionsupporting
confidence: 77%
“…Albumin most probably provides therapeutic benefits for spinal cord injury when administered alone [21] . Indeed the replacement of cerebrospinal fluid with 8% albumin following experimental ischaemic experimental SCI can reduce motor deficits, although this has been attributed mainly to reduction of intraspinal oedema [87] . However evidence for direct penetrability of Alb-OA into the spinal parenchyma should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the naloxone effect might be mediated by suppression of excitatory neurotransmitters, and SFD might work by removing substances toxic to ischemic neurons (ie, endorphins, excitatory neurotransmitters, or other substances), thereby acting on the same final injury pathway. 21,22 We added barbiturate burst suppression in 1989 coincident with the elimination of nitroprusside for blood pressure control because of its negative effect on spinal cord blood flow and organ perfusion. 1,23,24 We also became more aggressive with moderate hypothermia, and by 1989, our protocol called for the core temperature to be less than 34 C before aortic occlusion; the core temperature decreased to 32 C to 33 C, an additional 1.5 C to 2 C, with cold renal perfusion.…”
mentioning
confidence: 99%
“…2 Certainly the pressure environment of the spinal cord critically influences neurological function, and so, under experimental conditions, relatively small absolute alterations in CSF pressure may have profound implications for how the spinal cord responds to insult. 3,4 However, it remains to be determined if vertebral position and/or motion within physiological limits alter CSF pressure and, furthermore, if SMT influences CSF pressure.…”
mentioning
confidence: 99%